Analysis of Health Service Performance at Loa Bakung Health CenterAfter Implementation The e-Puskesmas System - La Debi Atthoba; Ike Anggraeni; Ratno Adrianto (Faculty of Public Health Mulawarman University, Indonesia, 2025)
Background : Digital transformation is a key strategy in modernizing the health sector globally and nationally. In Indonesia, the implementation of health information systems such as E-Puskesmas aims to improve work efficiency, clinical data accuracy, service effectiveness at First-Level Health Facilities. Objective : This study analyzes the performance indicators of health services at UPTD Puskesmas Loa Bakung after the implementation of the E-Puskesmas system, focusing on service time efficiency, curative workload, and the achievement of promotive–preventive programs. Research Methods/ Implementation Methods : A descriptive approach was used based on secondary data from E-Puskesmas operational reports from January to September 2025. Data were obtained from individual service unit (UKP) reports, monthly BPJS Health reports, and public health program records. The analysis focused on operational efficiency, disease burden profiles, and priority program achievements. Results : Findings reveal a gap between digitalization goals and operational reality. Only 50.1% of patients were served within less than 10 minutes, indicating workflow bottlenecks. Essential Hypertension (2,985 cases), Acute Respiratory Infections (1,300 cases) dominated curative services, while screening achievements for Hypertension (16.43%) and Diabetes (4.10%) remained below targets. This reflects a reactive service orientation with limited promotive and preventive efforts. Conclusion/Lesson Learned : : E-Puskesmas has improved data recording accuracy but has not fully enhanced systemic performance. Optimization is needed through better network infrastructure, improved digital competence among health workers, and data-driven decision-making. Strategic focus should emphasize strengthening promotive and preventive programs as the core of primary health digital transformation.